The Business Sustainability of Micro, Small, and Medium Enterprises During the Covid-19 Era in Lampung - Bahruddin , Moh; Ulfa, Ghina; Kurniawan, Aceng (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
UMKM is one of the sectors that are heavily affected by the Covid-19 pandemic, while UMKM is one of the supporting factors that are quite promising, both for the state, individuals and business groups. This research includes field research that is carried out in the field in an actual setting. In this case, the researcher intends to explore, identify, analyze and explain various conditions related to the business strategy of UMKM business sustainibility in the market in carrying out the business continuity strategy achieved by UMKM actors in the Pasar Unit II Tulang Bawang, Pasar Metro, and Pasar Bambu Kuning. Bandar Lampung to maintain and increase its income during the Covid-19 pandemic while still paying attention to business ethics in Islam. UMKM actors take advantage of technology in expanding their business so that they can be of interest to the wider community. The introduction and knowledge of business actors to digital marketing must be further improved to encourage more effective and efficient promotion and marketing activities.